2015
DOI: 10.3892/ol.2015.3200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the receptor for advanced glycation end-products and frequency of polymorphism in lung cancer

Abstract: Abstract. Receptor for advanced glycation end products (RAGE) is associated with the pathogenesis of cancer progression. The pathological effects mediated through RAGE are physiologically inhibited by soluble RAGE (sRAGE). The aim of the present study was to identify the expression of the sRAGE, RAGE and RAGE ligands in serum samples and lung cancer tissue obtained from lung cancer patients. Using ELISA and immunohistochemistry, it was observed that the sRAGE levels were downregulated in the serum, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Moreover, it has been demonstrated that over-expression of RAGE in lung cancer cells reduces proliferation and tumor growth [28,122]. Paradoxically, although RAGE is decreased in lung cancer, its ligands, which are often associated with proliferative effects, are increased [123126] and are predictors of poor prognosis [127]. This may be due in part to the fact that the predominant cell-type in lung cancers is the bronchial epithelial cell, which does not typically express RAGE.…”
Section: Rage In Pulmonary Diseasesmentioning
confidence: 99%
“…Moreover, it has been demonstrated that over-expression of RAGE in lung cancer cells reduces proliferation and tumor growth [28,122]. Paradoxically, although RAGE is decreased in lung cancer, its ligands, which are often associated with proliferative effects, are increased [123126] and are predictors of poor prognosis [127]. This may be due in part to the fact that the predominant cell-type in lung cancers is the bronchial epithelial cell, which does not typically express RAGE.…”
Section: Rage In Pulmonary Diseasesmentioning
confidence: 99%
“…Although the role of HMGB1 in NSCLC is a research hotspot in recent years, the underlying molecular mechanisms for the HMGB1‐mediated progression, metas­tasis, and autophagy of lung cancer have not yet been fully elucidated. Many studies demonstrated that the combination of HMGB1 and RAGE was closely associated with the development of lung cancer . Normal human bronchial epithelial cells (NHBE) have the potency with NSCLC initiation in inflammatory microenvironment .…”
Section: Introductionmentioning
confidence: 99%
“…RAGE and its ligands are highly upregulated in cancer tissue (e.g., pancreatic, colon, and prostate cancer) [7]. By contrast, both RAGE and serum soluble RAGE (sRAGE) levels are downregulated in smokers and lung cancer patients [79]. …”
Section: Discussionmentioning
confidence: 99%
“…We were not able to monitor the clinical time course of serum sRAGE level as a surrogate marker in this case. There is speculation that downregulation of both RAGE and sRAGE may be a critical step in the formation of lung tumours [8, 9, 14]. Several genetic single nucleotide polymorphism (SNP) studies identified that the SNPs in the RAGE associated with increased NSCLC risk and a lower chemotherapy response rate and poor prognosis [9, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation